"Profoundly Cosmopolitan of Heart and Spirit"? Germans in the League of Nations Information Section - Leu, Hav P. (Culture and History: Student Research Papers, 2023)
Germany was a member of the League of Nations from 1926 to 1933. During that time, there were Germans employed at the Secretariat, and its Information Section, which had the greatest German presence, opened a small office to represent the League in Berlin. The League was founded on liberal internationalist ideals and its Covenant included a revolutionary article that opened all positions up to men and women equally. A biographical study of three German individuals associated with the Section and office reveals that ideological commitment to the League was not a given among all German employees, and gives insight into the interplay of gender, class and national – or international – identity. It also shows how the realities of who was employed in the Secretariat, and why, often hinged – despite the League’s ideological basis and the Covenant’s promise – on pragmatic and political considerations.